Using Thermography Infrared to Detect Diabetic Foot Ulcers in Asia Pacific Countries: Scoping Review - Haryanto, Haryanto; Surtikanti, Surtikanti; Ramadhaniyati, Ramadhaniyati; Junaidi, Junaidi; Ervita, Ledy; Magdalena, Maria; Oe, Makoto (Jurnal Pendidikan Keperawatan Indonesia, 2024)
Introduction: Diabetes Mellitus (DM) is a growing global health concern, particularly in Indonesia, where the prevalence is projected to rise significantly. Diabetic Foot Ulcer (DFU) is a severe complication of DM that escalates the risk of amputations. Early detection of DFUs plays a crucial role in preventing associated complications Objective: This review aimed to assess the efficacy of infrared thermography in detecting DFUs in the Asia-Pacific region. Methods: A scoping review methodology adhering to PRISMA guidelines was employed. Databases were searched from 2011-2021. PICO strategy used keyword Diabetic foot ulcer, Skin ulcer, Leg ulcer, Foot ulcer, Diabetic neuropathic, Thermography, Temperature mapping, and Detection from PubMed, Scopus, Google Scholar, and Science Direct. Quality of article assessed by JBI. Results: Four (4) studies meeting the inclusion criteria were identified, primarily cross-sectional in design. The results indicated promising sensitivity and specificity of infrared thermography in detecting DFUs among DM patients. The technology's ability to capture thermal images revealing temperature variations associated with tissue inflammation, a common DFU indicator, underscores its efficacy. This non-invasive technique allows for early detection and monitoring of DFUs, facilitating timely interventions and improving patient outcomes. Additionally, infrared thermography provides a quantitative and objective assessment of tissue health, complementing traditional visual inspection and palpation methods. Its effectiveness lies in detecting subtle skin temperature changes, aiding in early identification and management of DFUs before they progress to more severe stages. Conclusion: Infrared thermography shows significant potential in detecting DFUs early, which is vital for effective management and prevention of severe complications. Despite the promising results, broader and more rigorous studies are necessary to validate these findings across different populations and healthcare settings. Further research across diverse settings and study designs is essential to reinforce these findings.